Return-to-play guidelines for athletes after COVID-19 infection - reply - Phelan, D.; Kim, J. H.; Chung, E. H. (JAMA Cardiology, 2020)
In Reply We appreciate comments on our recent Viewpoint1 and the opportunity to respond to these important questions. Santos-Ferreira and colleagues recommend that coronavirus disease 2019 (COVID-19) return-to-play guidelines should emphasize symptoms and retesting. In terms of the controversy of retesting, recent data report recovered and noninfectious patients may shed detectable severe acute respiratory syndrome coronavirus 2 RNA for up to 3 months.2 Further, persons with mild to moderate COVID-19 infection do not appear to be infectious after 10 days following symptom onset; persons with more severe illness are likely not infectious after 20 days following symptom onset.